(untitled) (Revista Innova Educación, 2021)
In education and especially in the training of professionals, it is essential to understand and specify the different ways of entering the practical world, where universities or higher education institutions should be promoters of this aspect. Due to this, the main objective of this research was to analyze within the framework of the practice of legal clinics as a divergent phenomenon, which is aimed at shaping an expansion of the dynamics in legal clinics operating in Colombia. For this, a descriptive and systematic study was carried out based on the analysis of the different academic results proposed throughout the development and implementation of this figure in the legal offices of universities in Colombia, without going into statistical depth. In the first place, a contextualization was carried out on its historical development; followed by the analysis of its implementation as a divergent phenomenon and finally the implications and the needs to maintain constant innovation for the training of professionals adapted to the new social realities were mentioned.